KAJIAN PENERAPAN GOOD MANUFACTURING PRACTICES (GMP) PADA PENGOLAHAN KERIPIK PISANG - Dhian Herdhiansyah; Gustina Gustina; Andi Besse Patadjai; Asriani asriani (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The purpose of this study was to examine the application of Good Manufacturing Practices (GMP) in banana chip processing in Konda District. Research data were collected by (a) field studies (observation, interviews, and documentation); and (b) literature study. The results showed that the processing of banana chips in Konda District was sufficient to apply GMP with an application rate of 74.06% of the average application of GMP aspects, namely: (1) location and production environment 90.00%; (2) buildings and facilities 48.48%; (3) production equipment 88.88%; (4) water supply or water supply facilities 100.00%; (5) hygiene and sanitation facilities and activities 73.91%; (6) employee health and hygiene 68.18%; (7) maintenance and hygiene and sanitation programs 57.69%; (8) storage of 84.00%; (9) process control 74.07%; (10) food labeling 87.50%; (11) supervision by the person in charge of 80.00%; (12) 50.00% product withdrawal; (13) recording and documentation 35.71%; and (14) 100.00% employee training.